2015
DOI: 10.1002/pbc.25795
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Medication Adherence as a Standard of Care in Pediatric Oncology

Abstract: Poor adherence to pediatric cancer treatment protocols may prevent children and adolescents from realizing the potential benefits of therapy. This paper presents the evidence for a standard of care for supporting medication adherence. Databases were reviewed for articles examining adherence and including children and/or adolescents with cancer. Fourteen articles (i.e., qualitative, quantitative, review, and randomized clinical trials) were evaluated for rigor.There is moderate-quality evidence to support a str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 24 publications
0
33
0
1
Order By: Relevance
“…Among studies that included AYAs, reported rates of nonadherence range from 23% to 63% . These data suggest significant potential for intervention, and given the lack of clear predictors of nonadherence, emphasize the importance of universal assessment of adherence among all AYAs . Without a formal adherence assessment, physicians correctly identified nonadherence less than 50% of the time …”
Section: Determining Adherencementioning
confidence: 97%
See 3 more Smart Citations
“…Among studies that included AYAs, reported rates of nonadherence range from 23% to 63% . These data suggest significant potential for intervention, and given the lack of clear predictors of nonadherence, emphasize the importance of universal assessment of adherence among all AYAs . Without a formal adherence assessment, physicians correctly identified nonadherence less than 50% of the time …”
Section: Determining Adherencementioning
confidence: 97%
“…Finally, “forgetting” to take medications is a frequently cited barrier to adherence among the AYA population . Adolescents are neurodevelopmentally less future oriented than adults and have a different approach to managing and prioritizing competing demands .…”
Section: Dimensions Of Aya Adherencementioning
confidence: 99%
See 2 more Smart Citations
“…The multidisciplinary Psychosocial Standards of Care Project for Childhood Cancer (PSCPCC), consisting of more than 80 oncology professionals and parent advocates, and supported by the Mattie Miracle Foundation (http://www.mattiemiracle.com), developed a set of 15 evidence‐based Standards for Psychosocial Care for Children with Cancer and Their Families that are endorsed by key professional organizations. The first 14 cover the following aspects of clinical care: assessment of psychosocial healthcare needs (PSS1); monitoring of neuropsychological deficits (PSS2); screening in long‐term survivorship (PSS3); psychosocial support and interventions (PSS4); assessment of financial need (PSS5); parental mental health (PSS6); psychoeducation, information, and anticipatory guidance (PSS7); preparatory information for procedures (PSS8); opportunities for social interaction (PSS9); sibling support (PSS10); school support (PSS11); facilitating adherence to treatment (PSS12); palliative care/end of life care (PSS13); and bereavement care (PSS14) . The full set of Standards is included as Supplementary Material S1.…”
Section: Introductionmentioning
confidence: 99%